Role Of Zinc Supplementation in Growth and Neuro-Development of Premature and Small for Gestational Age (SGA) Babies - Manish Parakh; BD Gupta; Suman Bhansali; Poonam Parakh; Pramod Sharma; Manisha Gurjar; Narendra Chhangani (Medsci Publications, 2012)
Objectives: A negative Zinc balance exists in preterm and small for gestational age infants. The current study evaluates the role of zinc supplementation on growth and neurodevelopmental outcome of these infants. Methods: One hundred and twenty eight infants who were born either premature and/or small for gestational age were followed for six months. A detailed assessment of anthropometry, neurodevelopment and morbidity patterns due to Diarrhea and Acute Respiratory Infection were recorded during each visit. Results: At birth and at six months the mean serum Zinc level in the study and control group was 0.87±0.398, 1.03±0.567, 0.88±0.248, 0.83±0.355mg/L respectively. The SZnR 6/B is significantly higher in study group as compared to controls (1.153 ± 0.55 Vs 0.913±0.438, p<0.01) suggesting better maintained serum zinc levels in zinc supplemented infants. Zinc supplemented exclusively breast fed infants had significantly higher SZnR 6/B as compared to non supplemented exclusively breast fed infants (1.555±0.654 vs 0.850±0.406,p<0.01). Further Zinc supplemented exclusively breast fed infants had significantly higher SZnR 6/B as compared both Zinc supplemented mixed and top fed infants. No effect of zinc supplementation was observed on growth, neurodevelopmental out come and morbidity pattern due to Diarrhea and ARI. Conclusion: It can be concluded from the present study that zinc supplementation and exclusive breast feeding in premature and/or SGA infants results in better serum Zinc ratio. However Zinc supplementation has no role in the growth or neurodevelopmental outcome or morbidity patterns due to acute diarrhea and respiratory infections of premature and/or small for gestational age infants. But the breast milk has a definite value to improve morbidity patterns due to diarrhea in these infants.